2013
DOI: 10.1037/a0032877
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Monoamine Oxidase A gene (MAOA) predict free-riding behavior in women in a strategic public goods experiment.

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 83 publications
(132 reference statements)
0
8
1
Order By: Relevance
“…This division of people into distinct social types has been the accepted basis for new fields of research investigating the cultural, genetic, and neuronal bases of this variation (3)(4)(5)(6)(17)(18)(19)(20). Some studies have suggested these differences can be exploited by policies to make societies behave in a more public spirited way (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…This division of people into distinct social types has been the accepted basis for new fields of research investigating the cultural, genetic, and neuronal bases of this variation (3)(4)(5)(6)(17)(18)(19)(20). Some studies have suggested these differences can be exploited by policies to make societies behave in a more public spirited way (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…We aim to explore whether more refined measures of cooperative phenotypes—underlying strategies rather than observable actions—support the replicability and robustness of previously reported associations. We replicate the analysis of Mertins et al [ 27 ], by testing the association between cooperative strategies and MAOA- uVNTR variants in an admixed Latino population and extended it by including OXTR rs53576, and AVPR1a RS3 as additional candidates (n = 188).…”
Section: Introductionmentioning
confidence: 93%
“…Recent evidence supports the inheritability of cooperative strategies [ 11 ] and sheds light on its neurological basis [ 26 ]. To our knowledge, only Mertins et al [ 27 ] have reported association of a genetic variant with cooperative strategies, MAOA -uVNTR, located in the gene that codes for monoamine oxidase A, which metabolizes monoamine neurotransmitters. Variants in this gene lead to a lower expression (MAOA-L) or higher expression (MAOA-H) of monoamine oxidase A [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests that social preferences are partly hardwired. For example, genes have been proven to contribute to individual differences in cooperative behavior in experimental trust (Cesarini, Dawes, Fowler, Johannesson, Lichtenstein, & Wallace, 2008), dictator (Cesarini, Dawes, Johannesson, Lichtenstein, & Wallace, 2009) and public good games (Mertins, Schote, & Meyer, 2013). Thirdly, even if we yet do not fully believe that inclinations are stable by the end of a course of study, they should at least be predictive for behavior at the time of career entry, on which we focus.…”
Section: Introductionmentioning
confidence: 98%